Riba in Sharia Economic Law: A Bibliometric Study - Titania Mukti (Indonesian Journal of Law and Syariah, 2025)
Riba in the view of sharia economic law is expressly prohibited in the Quran and Hadith. Explanations related to Riba and its practice in society require a comprehensive research study. This research aims to conduct bibliometric analysis to visualize articles related to Riba in sharia economic law, find out research trends related to riba, evaluate the impact of research, and identify research networks in order to help stakeholders in making decisions on the practice of muamalah to avoid usury. This study presents a bibliometric analysis using VOSviewer software and the article data used is 200 Scopus-indexed articles collected from 1980 to 2023. The results of this study show that the keywords "Usury", "Islamic Finance", and "Islamic Law" are the most up-to-date keywords with the grand theme of the research, namely riba in Islamic economic law. The researchers who contributed the most were Hewkes D., Termin P., and Todeschini G. who have written 3 research papers. The research cluster consisting of 10 clusters shows the results of the direction of future research development. Future research recommendations researchers can take the theme of riba practices that can result in bankruptcy, a review of ethics in financial practices, and the law of riba in the Qur'an analysis and its implications.